Apakah Tradisi Antar Pakatan Bentuk Dari Praktik Akuntansi (Pendapatan dan Beban ?) - Herjiden; Indah Permata Sari; Fredi Handoko (Politeknik Caltex Riau, 2025)
This research aims to present accounting practices regarding the recognition of income and expenses in social reality, culture and traditions between alliances with the concept of matching. Marriage is a sacred and important event in human life which not only has social and cultural dimensions but includes economic dimensions. In this context, accounting practices play a role in recording and managing financial aspects related to antar pakatan traditions. Data analysis techniques with Symbolic interaction analysis with the aim of understanding how symbols, rituals, and actions in traditions and cultures have a certain meaning. The results of the study show that various accounting practices are related to the recognition of income and expenses in the tradition of antar pakatan. Income comes from gifts from family, relatives, and the community from the antar pakatan for the wedding organizer, while the expense is recognized when the expense is incurred both from the community who gives antar pakatan and the costs incurred by the party organizing the marriage. This accounting practice is more based on hereditary traditions but has its own value and meaning so that unique and diverse characteristics emerge. A deep understanding of this tradition is essential to contribute to the development of accounting that is more contextual and relevant to the needs of society.